2016
DOI: 10.15252/embj.201593499
|View full text |Cite
|
Sign up to set email alerts
|

SIRT 7 promotes genome integrity and modulates non‐homologous end joining DNA repair

Abstract: Sirtuins, a family of protein deacetylases, promote cellular homeostasis by mediating communication between cells and environment. The enzymatic activity of the mammalian sirtuin SIRT7 targets acetylated lysine in the N‐terminal tail of histone H3 (H3K18Ac), thus modulating chromatin structure and transcriptional competency. SIRT7 deletion is associated with reduced lifespan in mice through unknown mechanisms. Here, we show that SirT7‐knockout mice suffer from partial embryonic lethality and a progeroid‐like p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
248
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 236 publications
(273 citation statements)
references
References 81 publications
12
248
0
4
Order By: Relevance
“…Multiple studies have shown declines in SIRT activity or levels with age in different organisms, tissues, and cells types [41, 4852]. SIRT6 and SIRT7 knockout mice display progeroid phenotypes and have shorter lifespans than controls [53, 54], and SIRT3 polymorphisms have been associated with longevity in human populations [55]. Sirtuins play a protective role in multiple aging-related diseases including neurodegenerative disorders, hearing loss, cardiovascular disease, and disorders of glucose and lipid metabolism [21, 56, 57].…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 99%
“…Multiple studies have shown declines in SIRT activity or levels with age in different organisms, tissues, and cells types [41, 4852]. SIRT6 and SIRT7 knockout mice display progeroid phenotypes and have shorter lifespans than controls [53, 54], and SIRT3 polymorphisms have been associated with longevity in human populations [55]. Sirtuins play a protective role in multiple aging-related diseases including neurodegenerative disorders, hearing loss, cardiovascular disease, and disorders of glucose and lipid metabolism [21, 56, 57].…”
Section: Molecular Mechanisms Of Agingmentioning
confidence: 99%
“…The role of SIRT7 in regulating DNA damage remains largely dormant for years until recently Vazquez and colleagues uncovered a novel function of SIRT7 in DNA repair [111]. They noted that genome homeostasis is disrupted in the absence of SIRT7 and SIRT7 promotes DNA repair by deacetylating lysine 18 of histoneH3 (H3K18Ac) at DNA damage sites and then recruiting NHEJ repair factor 53BP1.…”
Section: Sirtuins In Metabolismmentioning
confidence: 99%
“…Furthermore, SIRT7 is also shown to be an activator that stimulates ribosomal biogenesis in dividing cells (Tsai et al, 2014) by activating rDNA transcription through multiple mechanisms (Chen et al, 2016; Ford et al, 2006; Tsai et al, 2012), thereby supporting the high biosynthetic and metabolic demands of cancer cells. Recent studies also show that SIRT7 can modulate DNA repair and maintain genome integrity (Li et al, 2016; Vazquez et al, 2016). In addition to its role in cancer, SIRT7 also plays an important role in the regulation of cell death and damage by inhibiting p53, Ras, and Akt signaling pathways in the heart (Vakhrusheva et al, 2008a; Vakhrusheva et al, 2008b).…”
Section: Introductionmentioning
confidence: 99%